An analysis of pharmacy workforce capacity in Saudi Arabia - Almaghaslah, Dalia (Frontiers in Pharmacology, 2023)
Background: Previous reports have highlighted the core issues with the intelligence of the national pharmacy workforce reliance on non-native pharmacists, despite the increasing supply of local pharmacy graduates; limited participation of female pharmacists in the workforce; and inadequate proportions of pharmacists in primary healthcare centres, resulting in pharmaceutical services being provided without a pharmacist’s supervision. Methods: The current study used a retrospective cross-sectional design and data was collected from January to May 2023. Data was retrieved from the Health Statistics Yearbook, 2017, 2018, 2019, 2020 and 2021. The data included the total number of pharmacists, the number of Saudi pharmacists, the number of foreign pharmacists, the distribution of the proportions of male and female pharmacists, and the distribution of the workforce by region, sector and nationality. Data was also obtained relating to pharmacy education, including the number of pharmacy colleges, the number of pharmacy students and the number of pharmacy graduates. Results and conclusion: The capacity of the pharmacy workforce, meaning the number of pharmacists per 10,000 population, fluctuated between 2017 and 2021, with the lowest number being in 2020, a mere 7.9 pharmacists per 10,000 population. However, in 2021, the overall density of pharmacists increased to (9.04), which is above the global average (7.36 per 10,000 population). The proportion of women working in the pharmacy profession increased from 12% to 22%, and in community pharmacies from 0.3% to 7.2%, between 2016 and 2021. Another issue that still exists is a lack of proportionate and imbalance in the distribution of the pharmacy workforce across the regions. The renationalisation initiatives increased the overall proportion of Saudi pharmacists to 39% in 2021, compared to 22% in 2016. There is a need for a policy mechanism that will overcome the identified issues.